Dynamics of Protection of Intellectual Property Rights in Indonesia: Analyzing The Challenges and Future Prospects - Alifandi Risky Cahya Putra; Christine S.T. Kansil (Syntax Literate, 2022)
This article examines the dynamics of intellectual property rights (IPR) protection in the digital era in Indonesia, with a focus on the challenges of globalization and technological developments. This abstract summarizes crucial aspects such as regulation, public awareness, and the balance between innovation and protection in a digital context. Through in-depth analysis, this article identifies factors that influence the effectiveness of IPR protection and offers suggestions for maintaining an optimal balance in the digital environment.